Can laboratory and clinical parameters predict the occurrence of acute arterial occlusion in COVID-19 patients? - Kristian Karlović; Gojko Bogdan; Pejana Rastović; Martin Kajić (Medicinski glasnik, 2022)
Aim: To determine radiologic, clinic and laboratory characteristics of COVID-19 positive patients with acute arterial occlusion and compare them with post COVID-19 and non-COVID-19 patients. Methods: In this retrospective study, 53 patients with acute occlusion of peripheral arteries admitted to the University Clinical Hospital Mostar in the period between 29 February 2020 and 30 September 2021 were involved. The first group was made of COVID-19 positive patients, the second group were post COVID-19 patients and a control group were non-COVID-19 patients. Results: Most patients were males, 37 (69.8%). The average age of COVID positive patients was 66.09±11.25 years, post COVID-19 patients 71.33±5.22 years and COVID-19 negative patients 69.82±1.99 years. Lower extremities were most affected, 38 (71.6%), without significant alteration in the coagulogram. Acute arterial occlusion occurred about 2 weeks after the beginning of COVID-19 or at the time of the first appearance of symptoms. Conclusion: We have to take special care about patients with risk factors for developing acute arterial occlusion due to thromboembolism or thrombosis 10 days after the beginning of the disease. We also recommend the use of low molecular weight heparin (LMWH) and monitoring coagulation state due to anti Xa and thromboelastometry.
Keywords: angiography; coronavirus; heparin; thromboembolism